On the preparation of EPDM-g-MAH compatibilizer via melt-blending method - A. Razak, J.; Mohamad, N.; Mahamood, M. A.; Jaafar, R.; Othman, I. S.; Ismail, M. M.; Tee, L. K.; Ramli, Junid; Mustafa, Z. (Faculty Mechanical Engineering, UMP, 2019)
This paper presents an experimental investigation to determine the optimum composition of maleic anhydride (MAH) and dicumyl peroxide (DCP) as initiator for ethylene-propylene-diene-monomer grafted MAH (EPDM-g-MAH) compatibilizer preparation, using response surface methodology (RSM) approach. EPDM-g-MAH was prepared in the laboratory scale by melt blending method using an internal mixer. For this study, the effects of MAH (2.50 – 7.50 wt.%) and DCP (0.10 – 0.30 wt.%) towards grafting efficiency was determined. Two level full factorial design of experiment (DOE) is applied to establish the relationship between these two independent factors of raw materials. Analysis of variance (ANOVA) and the optimization menu were utilized to decide the raw materials formulation with maximum grafting efficiency. Quantitative analysis based on infra-red (IR) spectral intensity supported by 1H-NMR spectral are used to propose for EPDM-g-MAH grafting mechanism. Standard calibration curve for quantity ratio plot was exponential with R2 = 89.19%. It was found that an optimum about 8.52% of MAF grafting efficiency has been yielded with DCP factor has contributed larger effect at 67.45% of contribution effect. Anhydride stretching of grafted C=O as confirmed by FTIR peak at 1713 cm-1 and 1770 – 1792 cm-1 has responsible for MAH grafting into EPDM rubber. Based on FTIR, 1H-NMR and 2D-COSY spectral analysis, reaction mechanism for EPDM-g-MAH grafting was successfully proposed with two possible termination steps.